Pengaruh Popularitas Influencer terhadap Niat Pembelian Scarlett Whitening Melalui Sikap Influencer - Silvia, Gina; Putra, Harmanda Berima (J-MAS (Jurnal Manajemen dan Sains), 2024)
This research aims to analyze the influence of influencer popularity on purchase intemtions for Scarlett Whitening through the influencer’s attitude. The data collection method for this research uses primary data. The population used in this research is the general public who intend to purchase Scarlett Whitening products. This research uses a purposive sampling technique and the sample size in the research is 150 respondents. This research model uses the Structural Equation Modeling (SEM) model as a test tool, namely Partial Least Square (PLS). the results of this research show that the popularity of influencers has a positive effect on purchase intentions. The influencer’s attitude has a positive effect on purchase intentions and the influencer’s popularity through the influencer’s attitude has a positive effect on purchase intentions.